PERJANJIAN UTANG-PIUTANG EMAS DALAM HUKUM ISLAM (STUDI PADA MASYARAKAT DI KECAMATAN MILA KABUPATEN PIDIE PROVINSI ACEH) - CUT DINDA MUSTIKA (PREMISE LAW JURNAL, 2017)
The research results show that Paying off the debt with the same amount of gold borrowed and some adjustment to the gold price when borrowed is permitted, because it is in line with the Islamic Sharia. Observed from the pillars and terms of the debt and credit agreement using gold, the debt and credit are eligible because shighat agreement has been made; capable of taking legal action; the object is in the form of property possessed by an individual and it has value according to the Sharia. Meanwhile, as to the murtahin who makes profit from the collateral possessed by the rahin, it is not in accordance with the Islamic Law. The use of the marhun (collateral) remains the right of the rahin because principally the position of collateral in debt and credit agreement is as the trust guarantee for the debt, not to gain some profit. Keywords: Agreement of Debt and Credit Using Gold, Mortgage, Islamic Law